Waterborne Cd2+ weakens the immune responses of blood clam through impacting Ca2+ signaling and Ca2+ related apoptosis pathways. Issue 77 (June 2018) - Shi, Wei; Guan, Xiaofan; Han, Yu; Guo, Cheng; Rong, Jiahuan; Su, Wenhao; Zha, Shanjie; Wang, Yichen; Liu, Guangxu
Abstract: Exposure to heavy metals such as Cadmium (Cd) may exert detrimental impacts on the immune responses of marine bivalve species. However, the immunotoxicity of Cd on blood clams remains unknown to date. Furthermore, though Cd 2+ is known to compete with calcium (Ca 2+ ) ions for their binding sites in cells and inhibit Ca 2+ influx, whether Cd 2+ weakens the immune responses of marine bivalves through inducing intracellular Ca 2+ disorders still remains unclear. Therefore, the immunotoxicity of Cd 2+ at different waterborne Ca 2+ concentrations on blood clam, Tegillarca granosa, were investigated in the present study. Results obtained demonstrated that the total number, phagocytic activity, and red granulocytes ratio of the haemocytes were all significantly reduced after 10 days exposure of individuals to 25 μg/L Cd 2+ . However, when the waterborne Ca 2+ concentrations were elevated by 10% and 20% (approximately 370 and 410 mg/L, respectively), mitigation effects on the immune responses of individuals were detected. In addition, though the expressions of genes from the Ca 2+ signaling and Ca 2+ -related apoptosis pathways were significantly altered by Cd 2+ exposure, the expression patterns of these genes were similar to that of the control when the waterborne Ca 2+ concentrations were elevated, suggesting a relieving effect of waterborne Ca 2+ on Cd 2+ induced toxicity to haemocytes. The results obtained in the present study revealed that waterborne Cd 2+ may hamper the immune responses of T. granosa through influencing Ca 2+ signaling and Ca 2+ -related apoptosis pathways, which can be partially mitigated by elevating the waterborne Ca 2+ concentrations. Highlights: Cd 2+ exposure induced a reduction in total haemocytes counts and phagocytosis. Cd 2+ exposure affected the expressions of genes from the Ca 2+ signaling pathway. Cd 2+ exposure influenced the Ca 2+ -related apoptosis pathways. Elevated waterborne Ca 2+ concentrations can relieve the immunotoxicity of Cd 2+ .